Amnesty And Abolition From The Perspective Of Fiqh Jinayah: Implications For The Modern Criminal Justice System - Achmad Kholiq; Anne Haerany (Ann Publisher, 2025)
Background. This article discusses the concepts of amnesty and abolition from the perspective of fiqh al-jinayah (Islamic criminal law), and their relevance to the dynamics of the modern criminal justice system. In a positive legal system, amnesty and abolition are legal instruments that give the head of state the authority to halt or end criminal proceedings against specific individuals or groups in the public interest, such as political reconciliation or national stability. Aims. However, in the context of fiqh jinayah, similar concepts are found in the form of ʿafw (forgiveness), ṣulḥ (reconciliation), and takwīf al-ḥadd (suspension of execution), each of which has normative limitations based on the rights of Allah (ḥuqūq Allāh) and human rights (ḥuqūq al-'ibād). Methods. This article uses a qualitative-normative approach, with comparative and hermeneutic analyses of classical and contemporary fiqh. Result. The results of the study show that Islam opens space for forgiveness in the criminal realm, especially in the categories of ta'zīr and some qiṣāṣ, while still emphasizing substantive justice as the main principle. Conclusion. In the context of the modern criminal justice system, the redefinition of amnesty and abolition within the framework of maqāṣid al-syarī'ah is essential to prevent abuse of authority while guaranteeing the rights of victims and the public benefit.